Non-convulsive Status Epilepticus in SEMA6B-Related Progressive Myoclonic Epilepsy: A Case Report With Literature Review - Duan, Jing; Chen, Yan; Hu, Zhanqi; Ye, Yuanzhen; Zhang, Tian; Li, Cong; Zeng, Qi; Zhao, Xia; Mai, Jiahui; Sun, Yang; Liu, Chao; Zheng, Wenxin; et al. (Frontiers in Pediatrics, 2022)
Progressive myoclonic epilepsy (PME) is a group of rare diseases characterized by progressive myoclonus, cognitive impairment, ataxia, and other neurologic deficits. PME has high genetic heterogeneity, and more than 40 genes are reportedly associated with this disorder. SEMA6B encodes a member of the semaphorin family and was first reported to cause PME in 2020. Herein, we present a rare case of PME due to a novel SEMA6B gene mutation in a 6-year-old boy born to healthy nonconsanguineous Chinese parents. His developmental milestones were delayed, and he developed recurrent atonic seizures and myoclonic seizures without fever at 3 years and 11 months of age. He experienced recurrent myoclonic seizures, nonconvulsive status epilepticus (NCSE), atonic seizures, and atypical absence seizures during the last 2 years. At different time points since onset, valproic acid, levetiracetam, piracetam, and clobazam were used to control the intractable seizures. Notably, NCSE was controlled by a combination of piracetam with clobazam and valproic acid instead of intravenous infusion of midazolam and phenobarbital. Due to the limited number of cases reported to date, the clinical description of our case provides a better understanding of the genotype–phenotype correlations associated with PME and indicate that piracetam may be effective against NCSE in patients with SEMA6B-related PME.